Clathrin- and Caveolin-Independent Entry of Human Papillomavirus Type 16—Involvement of Tetraspanin-Enriched Microdomains (TEMs) - Spoden, Gilles (Public Library of Science, 2008)
BACKGROUND: Infectious entry of human papillomaviruses into their host cells is an important step in the viral life cycle. For cell binding these viruses use proteoglycans as initial attachment sites. Subsequent transfer to a secondary receptor molecule seems to be involved in virus uptake. Depending on the papillomavirus subtype, it has been reported that entry occurs by clathrin- or caveolin-mediated mechanisms. Regarding human papillomavirus type 16 (HPV16), the primary etiologic agent for development of cervical cancer, clathrin-mediated endocytosis was described as infectious entry pathway. METHODOLOGY/PRINCIPAL FINDINGS: Using immunofluorescence and infection studies we show in contrast to published data that infectious entry of HPV16 occurs in a clathrin- and caveolin-independent manner. Inhibition of clathrin- and caveolin/raft-dependent endocytic pathways by dominant-negative mutants and siRNA-mediated knockdown, as well as inhibition of dynamin function, did not impair infection. Rather, we provide evidence for involvement of tetraspanin-enriched microdomains (TEMs) in HPV16 endocytosis. Following cell attachment, HPV16 particles colocalized with the tetraspanins CD63 and CD151 on the cell surface. Notably, tetraspanin-specific antibodies and siRNA inhibited HPV16 cell entry and infection, confirming the importance of TEMs for infectious endocytosis of HPV16. CONCLUSIONS/SIGNIFICANCE: Tetraspanins fulfill various roles in the life cycle of a number of important viral pathogens, including human immunodeficiency virus (HIV) and hepatitis C virus (HCV). However, their involvement in endocytosis of viral particles has not been proven. Our data indicate TEMs as a novel clathrin- and caveolin-independent invasion route for viral pathogens and especially HPV16.